Physiological Effects and Inter-Individual Variability to 12 Weeks of High Intensity-Interval Training and Dietary Energy Restriction in Overweight/Obese Adult Women - Andrade-Mayorga, Omar; Martínez-Maturana, Nicolás; Salazar, Luis A.; Díaz, Erik (Frontiers in Physiology, 2021)
Background: Human adaptive response to exercise interventions is often described as group average and standard deviation to represent the typical response for most individuals, but studies reporting individual responses to exercise show a wide range of responses. Objective: To characterize the physiological effects and inter-individual variability on fat mass and other health-related and physical performance outcomes after 12 weeks of high-intensity interval training (HIIT) and dietary energy restriction in overweight/obese adult women. Methods: Thirty untrained adult overweight and obese women (age= 27.4 ± 7.9 yrs; BMI= 29.9 ± 3.3 kg/m2) successfully completed a 12-week supervised HIIT program and an individually prescribed home hypocaloric diet (75% of daily energy requirements) throughout the whole intervention. Results: The prevalence for high and low responders was 33% (N=11) and 66% (N=19), respectively. At the whole group level, the intervention was effective to reduce the absolute fat mass (30.9±7.2 vs. 28.5±7.2 kg; P<0.0001), body fat percentage (39.8±4.3 vs. 37.8±4.9 %; P<0.0001), total body mass (76.7±10.1 vs. 74.4±9.9 kg; P<0.0001). In addition, there were improvements in systolic blood pressure (Δ%= -5.1%), diastolic blood pressure (Δ%= -6.4%), absolute VO2peak (Δ%= +14.0%), relative VO2peak (Δ%= +13.8%), peak power output (Δ%= +19.8%), anaerobic threshold (Δ%= +16.7%), maximal ventilation (Δ%= +14.1%), and peak oxygen pulse (Δ%= +10.4%). However, at the individual level, a wide range of effects was appreciated on all variables, and the magnitude of the fat mass changes did not correlate with baseline body mass or fat mass. Conclusions: A 12-week supervised HIIT program added to a slight dietary energy restriction effectively improved fat mass, body mass, blood pressure, and cardiorespiratory fitness. However, a wide range of inter-individual variability was observed in the adaptative response to the intervention. Furthermore, subjects classified as low responders for fat mass reduction could be high responders in many other health-related and physical performance outcomes. Thus, the beneficial effects of exercise in obese and overweight women go further beyond the adaptive response to a single outcome variable such as fat mass or total body mass reduction.